Phytochemical Profile, Antioxidant Activity, and Cell Viability of Aegle marmelos Fruit Pulp Ethanolic Extract on SKOV-3 Ovarian Cancer Cells - Sri Wahyuni; EM Sutrisna; Maryati Maryati; Sari Haryanti; Rona Nasywa Mahira (LPPM Akafarma Sunan Giri Ponorogo, 2026)
Ovarian cancer remains a leading cause of cancer related mortality among women, emphasizing the need for safer more effective therapeutic strategies. Natural products are increasingly explored due to their diverse bioactive compounds. This study evaluated the phytochemical profile, total phenolic content (TPC), antioxidant activity, and cytotoxic effects of the ethanolic extract of Aegle marmelos fruit pulp on SKOV-3 ovarian cancer cells. Phytochemical screening was conducted using standard qualitative methods. TPC was determined by Folin-Ciocalteu Assay, antioxidant activity by the DPPH method, and cytotoxic using MTT assay. The extract contained flavonoids, alkaloids, tannins, and triterpenoids. The TPC was 8.22 mg GAE / g extract, indicating relatively low phenolic content. Consistently, antioxidant activity was week, with an IC50 value of approximately 712 ppm. The extract did not significantly reduce SKOV-3 cell viability, which remained above 90% at all tested concentrations. However, morphological changes, including cell shrinkage dan reduce adhesion, were observed at higher concentrations, suggesting sublethal cellular stress responses. In conclusion, the ethanolic extract of Aegle marmelos fruit pulp exhibits the presence of bioactive compounds and limited biological activity but lacks strong cytotoxic effects against SKOV-3 cells. These findings indicate its potential role as chemopreventive or supportive agent rather than a primary anticancer compound. Further studies are required to identify active constituents and clarify underlying mechanism.